2020
DOI: 10.1101/2020.09.15.298711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Latency and amplitude of the stop-signal P3 event-related potential are related to inhibitory GABAaactivity in primary motor cortex

Abstract: By stopping actions even after their initiation, humans can adapt their ongoing behavior rapidly to changing environmental circumstances. The neural processes underlying the implementation of rapid action-stopping are still controversially discussed. In the early 1990s, a fronto-central P3 event-related potential (ERP) was identified in the human EEG response following stop-signals in the classic stop-signal task, accompanied by the proposal that this ERP reflects the “inhibitory” side of the purported horse-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Moreover, Nguyen et al (2019) observed that P3 amplitude scaled with force measurements during failed stopping, so that smaller P3s were associated with greater force (and therefore greater response error). The P3's links to the motor system have been further corroborated in a study by Hynd et al (2020), which demonstrated that P3 amplitude relates to inhibitory GABA activity in motor cortex: subjects with higher levels of inhibitory GABAa activity (measured using short-interval intracortical inhibition) showed larger and earlier P3 ERPs following stop signals.…”
Section: 24mentioning
confidence: 67%
“…Moreover, Nguyen et al (2019) observed that P3 amplitude scaled with force measurements during failed stopping, so that smaller P3s were associated with greater force (and therefore greater response error). The P3's links to the motor system have been further corroborated in a study by Hynd et al (2020), which demonstrated that P3 amplitude relates to inhibitory GABA activity in motor cortex: subjects with higher levels of inhibitory GABAa activity (measured using short-interval intracortical inhibition) showed larger and earlier P3 ERPs following stop signals.…”
Section: 24mentioning
confidence: 67%
“…Whereas such correlations between inhibition performance and N2/P3 ERPs and the related time-frequency patterns are robust and reproducible, similar correlations have also been reported between these EEG indices and multiple other behavioral measures, thus questioning their specificity in indexing inhibitory processes per se (Huster et al, 2020). Hence, EEG correlates could either truly reflect a, say, "pure" inhibitory process (Hynd et al, 2020;Wessel and Aron, 2015), or the processing of the conflict required to inhibit action (Enriquez-Geppert et al, 2010), or a contextual update of the situation requiring a sporadic action revision (Waller et al, 2019). Thus, studying inhibition-related EEG patterns in tasks known to differ in the engaged action-control processes, as it is the case for discrete and rhythmic actions, may provide additional information to a functional interpretation of these EEG correlates.…”
Section: Introductionmentioning
confidence: 75%
“…Whereas such correlations between inhibition performance and N2/P3 ERPs and the related timefrequency patterns are robust and reproducible, similar correlations have also been reported between these EEG indices and multiple other behavioral measures, thus questioning their specificity in indexing inhibitory processes per se (Huster et al, 2020). Hence, EEG correlates could either truly reflect a, say, "pure" inhibitory process (Hynd et al, 2020;Wessel & Aron, 2015), or the processing of the conflict required to inhibit action (Enriquez-Geppert et al, 2010), or a contextual update of the situation requiring an sporadic action revision (Waller et al, 2019). Thus, studying inhibition-related EEG patterns in tasks known to differ in the engaged action-control processes, as it is the case for discrete and rhythmic actions, may provide additional information to a functional interpretation of these EEG correlates.…”
Section: Introductionmentioning
confidence: 76%